Obtenção de biomassa da macroalga agarófita Gracilaria birdiae (Plastino & Oliveira) através da germinação de esporos em condições de laboratório. - Holanda, Ticiana de Brito Lima (2016)
The species Gracilaria birdiae, widely used for agar extraction occurs in Brazilian tropical waters of the Ceará coast to the Espírito Santo. The objective of this work was to study the morphology, immunohistochemistry and reproduction of carpospores and tetraspores detailing all germination process. The histological cross sections of carposporophytic thallus G. birdiae allowed a better visualization of these reproductive structures. During the observation of stained slides, you could see that the cystocarps found themselves immature. Staining with Ponceau Xylidine (XP) pH 2.5 showed a low accumulation of proteins in the stem and a higher concentration of these macromolecules in cystocarp, especially in fusion cells and formed carpospores. Since the toluidine blue assay (AT) provided indicative of the presence of anionic radicals in cortical cells. The test Periodic Acid Schiff (PAS) showed increased accumulation of neutral polysaccharides in the cell wall and carpospores where such results were confirmed using Lugol test, which revealed the presence of floridean starch. The stem carposporophytic analysis G. birdiae by confocal microscopy revealed the morphology of the thylakoids by auto-fluorescence R-phycoerythrin. Three-dimensional images of the released carpospores revealed that the shapes of the thylakoids of gonimoblast have a unity aspect, balled and that fills much of the carpospore. The thylakoid terasporangium resembles those found in the analyzed carpospores. The largest amount of carpospores released from G. birdiae found on the first day of the experiment, where there was a release of 1,751 carpospores by cystocarp. Soon after the release, the carpospores settled and started the germination process. The carpospores have spherical shape, are well pigmented (slightly reddish) and the diameter averaged 22.30 ± 2.4 µm. The first division occurred soon after fixing the substrate, where the carpospore was divided in half to form two identical planes. Within 2-3 days without volume expansion, they gave rise to the stages tri- and tetra cell. After 4-5 days, the divisions were formed more rapidly giving rise to multicellular disks where the disks size average was 26.91 µm (± 3.13). In the experiment carried out with tetrasporophytic stems after 21 days of cultivation was viewing a light reddish surface over all the limestone of the groups. After addition of 0.1% of BAP and subjected to constant aeration through porous limestone aeration system and, after a period of 20 days was observed the formation of microthalli gametophytes only on the limestone, totaling a period of 3 months from the beginning of the experiment with the release and uptake of tetraspores until the formation of gametophytes microthalli. It was observed a difference in the germination of carpospores and tetraspores where we tetraspores the germination of filamentous type, where such filaments generated microtalli gametophytic. In conclusion we can say that G. birdiae stalks showed accumulation of anionic polysaccharides, starch and proteins in reproductive structures, as well as differences in the morphology of thylakoids. Moreover, obtaining algal biomass was possible (microthalli) from the tetraspores and carpospores germination cultivation under conditions established in the laboratory.